Application of the Connect Running Game Method to Improve Physical Education Learning Outcomes in Grade IV Students of SDN 84 Bengkulu City - Fellby M. Alvionsya; Juwita Juwita; Dolly Apriansyah (Sinar Sport Journal, 2023)
The purpose of this study was to see the application of the continuous running game method in improving physical education learning outcomes for fourth grade students at SD Negeri 84 Bengkulu City. In this study, the Classroom Action Research (CAR) method was used. The subject of this research is the fourth grade students at SD Negeri 84 Bengkulu City as many as 28 people. Data collection techniques used in the study were observation sheets and student test methods. Analysis of the data used values ​​are (1) Pre-test and Post-test analysis, (2) t-test analysis of Student Learning Outcomes. The instrument for validating the student's continuous running game in the research used was the Linkert scale model. The conclusion of this research is the application of the continuous running game method can improve physical education learning outcomes with the results of the t-test test in the first cycle is the t test results obtained obtained t arithmetic > from t table with t count = 3.946 and t table = 1.703 and the second cycle is obtained obtained t count > from t table with t count = 11,199 and t table = 1,703. The application of the game can improve the learning outcomes of fourth grade students of SD Negeri 84 Bengkulu City on the subject of Physical Education.